PENDIDIKAN HUKUM HINDU MEMBENTUK MORALITAS MANUSIA HINDU DALAM INTERAKSI SOSIAL - I Made Kastama (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The purpose of this paper is to explain Hindu law education to shape Hindu human morality, where Hindu law is a rule of law that is mostly contained in the Manawadharmasastra and a tradition passed down from generation to generation known as Sadacara. This writing use normative legal method, namely library research to obtain the secondary data. The data collected through studies literature with study and analyze data in accordance with the problem. The study results show Hindu law education made guidelines in social interactions neither for religious ceremony nor social activity committed by members of Hindu community by studying Hindu law books through non-formal education. Hindu community members become more discipline in thinking, speaking and acting (Tri Kaya Parisuda). The obedience against the rules of Hindu law becomes an obligation that must be carried out voluntarily, to maintain social order and avoid conflicts that exist in society.Keywords: Hindu Law Education, Social Interaction